Nurturing care practices for children with developmental disabilities in sub-Saharan Africa: A scoping review protocol. - Silas Onyango; Margaret Nampijja; Paul Otwate; Nelson Langat; Linda Oloo; Kenneth Okelo; Patricia Kitsao-Wekulo (PLoS ONE)
Background The majority of children with neurodevelopmental disorders (NDDs) reside in low- and middle-income countries (LMICs). NDDs are a public health concern in countries in sub-Saharan Africa (SSA). Nurturing care has been recommended as a pathway for addressing the developmental needs and unlocking the full potential of children, including those with NDDs. However, little information exists on the strategies to support children with NDDs using the Nurturing Care Framework in many countries in SSA. This review aims to synthesize information on nurturing care practices for children with NDDs in SSA. The review will also determine gaps in the provision of nurturing care for children with NDDs. Further, the review will highlight the drivers of care as well as the experiences of the caregivers. Methods The review will be implemented in six steps: specification of the research question, identification of relevant studies, selection of studies to be included, extracting, mapping, and charting the data, collating, summarizing, and reporting the results, and stakeholder consultation. We propose a database search followed by a manual search for the literature synthesis. We will search the following electronic databases: PubMed, ScienceDirect, Scopus, Open Grey and African Journals Online (AJOL). All studies published after May 2018 to May 2023 that include relevant terms will be identified and included. The research team will develop a data extraction form for use in capturing relevant information from each of the included studies. A patterning chart that will summarize and analyze the key findings of each article will be created. Discussion We anticipate that the study will provide evidence on the existing nurturing care practices and unearth gaps in the provision of nurturing care for children with NDDs. Key determinants of care and the experiences of the parents/caregivers of children will also be identified. The study will provide key recommendations on interventions to improve the quality of care for children with NDDs. Through this study, awareness of the unmet nurturing care needs of these children will be increased. The evidence generated may assist policymakers and stakeholders in addressing the needs of children with NDDs.